2021
DOI: 10.1186/s12969-021-00642-x
|View full text |Cite
|
Sign up to set email alerts
|

How children with juvenile idiopathic arthritis view participation and communication in healthcare encounters: a qualitative study

Abstract: Background Children report that they do not participate in their healthcare as much as they want, despite having the lawful right to form their own views and the right to express those views freely in all matters affecting them. Children and parents appeared to be more satisfied when healthcare professionals (HCP) use a participatory style in healthcare encounters. Aim To explore how children, adolescents and young adults with Juvenile Idiopathic A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
2
7
0
2
Order By: Relevance
“…This study extends findings established in previous research about the roles and values of parents in relaying information to healthcare professionals (Lundberg et al, 2021). Similar to our study, Lundberg et al (2021) found mixed perspectives from children and adolescents about the value of parents in pain communication. In this research, some children and adolescents believed parents provided a useful external perspective and they spoke to them frequently about their pain.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This study extends findings established in previous research about the roles and values of parents in relaying information to healthcare professionals (Lundberg et al, 2021). Similar to our study, Lundberg et al (2021) found mixed perspectives from children and adolescents about the value of parents in pain communication. In this research, some children and adolescents believed parents provided a useful external perspective and they spoke to them frequently about their pain.…”
Section: Discussionsupporting
confidence: 91%
“…This study extends findings established in previous research about the roles and values of parents in relaying information to healthcare professionals (Lundberg et al, 2021 ). Similar to our study, Lundberg et al ( 2021 ) found mixed perspectives from children and adolescents about the value of parents in pain communication.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The desire to protect children, particularly those who are vulnerable, is strong but can result in boundaries around children that silence them (James et al., 2007). Despite the reported benefits of being included in healthcare decision‐making (Bjønness et al., 2020; David et al., 2018; Miller & Jawad, 2019) and children's capacity and desire to have a voice in their care (Coyne & Gallagher, 2011; Foster et al., 2022; Kilkelly & Donnelly, 2006; Viksveen et al., 2022), children are still routinely excluded (Coyne et al., 2014; Kilkelly & Donnelly, 2011; Lundberg et al., 2021; O'Connor et al., 2021). Additionally, children's views are often excluded from service evaluations, even when the views of their parents are taken into consideration (Nordlind et al., 2022; Schalkers et al., 2016; Starlight Children's Foundation, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Especially if the child is still young, they can still be affected and sensitive to the things around him. So, the role of parents is needed and essential for children (Lundberg et al, 2021).…”
Section: Introductionmentioning
confidence: 99%